Friday

April 18, 2014

April 18, 2014

Posted by **Joy** on Tuesday, July 30, 2013 at 6:56am.

( 1 -2) (-5 6) (a b)

( 3 4) (7 -8) = (c d)

- Discrete Mathematics -
**Graham**, Tuesday, July 30, 2013 at 9:37amJust multiply the matrices

a = (1)(-5)+(-2)(7)

b = (1)(6)+(-2)(-8)

c = (3)(-5)+(3)(7)

d = (3)(6)+(3)(-8)

- Discrete Mathematics -
**Joy**, Tuesday, July 30, 2013 at 1:08pmFor the matrices I came up with the following:

a. -5 + -14 = -19

b. 6 + 16 = 22

c. -15 + 21 = 6

d 18 + -24 = -6

Is this right? What am I suppose to do afterwards?

**Related Questions**

Discrete Mathematics - What is the value of a that would make the matrix ...

mathematics - 4 distinct integers p, q, r and s are chosen from the set {1,2,3...

Discrete Mathematics - If f(x) = log2 (x - 2)3 and g(x) = log8 (x - 2), when is...

Discrete Mathematics - A 24 pack of soda costs $8 each and bags of chips cost $6...

Discrete Mathematics - Let p and q be propositions. Use Logical equivalences to ...

Discrete Mathematics - Let m,n,z belong to N such that m and n divide z and gcd...

discrete mathematics - Prove that a square of an integer ends with a 0, 1, 4, 5 ...

Discrete Mathematics - Show that the square of an oddnumber is an odd number ...

Discrete Mathematics - Prove that if n is an odd positive integer, then 1 ≡...

Discrete Mathematics (computer science) - Find a formula for the nth term of the...